Persuasive e-learning portal for Arabic language: ArabKafa3 / Siti Saudah Mohd Ghani ... [et al.] - Mohd Ghani, Siti Saudah; Johan, Elly Johana; Mohamed Yusuf, Syarifah Adilah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina (Unit Penerbitan JSKM, 2023)
The Al-Quran and Fardu Ain Class Program (KAFA) has been in place since 1990 with the goal of strengthening the foundations of Islamic education for children aged 7 to 12. The approach stresses reading the Al-Quran with tajwid and strengthening Fardu Ain's principles among his students, including knowledge of Arabic and writing Jawi. If students are not fluent in Jawi, they will have difficulty reading and understanding Arabic. In the context of teaching and learning Arabic, students are found to be less interested in learning and mastering the language. In this pandemic era, learning portals are quickly becoming one of the most popular learning tools. Technology was designed to help students learn, but there are times when the technology highlighted is not focused on achieving an objective and is not specifically designed, causing students to become disoriented. Students nowadays frequently face attitudinal issues such as difficulty focusing in purely online situations, boredom, isolation, and a lack of self-regulation. Recognizing the problem and the positive impact of persuasive technology in education, an Arabic language e-learning portal (ArabKafa3) will be developed through the adaptation of persuasive technology involving the principles of tunneling, liking, self-monitoring and cooperation. The ArabKafa3 scope focuses on several topics related to the Arabic language syllabus for third-year KAFA students. The ADDIE Model methodology is used to develop ArabKafa3, and the interface design of the ArabKafa3 based on persuasive technology principles is discussed in this study.